Oil spill environmental sensitivity mapping of Rio de Janeiro, Brazil - Rodrigues, Flávio Henrique; Kolya, André de Andrade [UNESP]; Veiga, Vinicius Mendes [UNESP]; dos Santos, Sara Felix [UNESP]; Wieczorek, Arthur [UNESP]; Corrêa, Claudia Vanessa dos Santos [UNESP]; Costa, Daiana Marques [UNESP]; Giordano, Lucília do Carmo [UNESP]; Riedel, Paulina Setti [UNESP]; Reis, Fábio A.G.V. [UNESP] (Elsevier, 2023)
The current case study focuses on the Environmental Sensitivity Index (ESI) mapping of Guanabara Bay, Rio de Janeiro, Brazil — a region at risk from petroleum sector pollution. By mapping 981.5 km of coastline and classifying it in 10 oil sensitivity indices, we integrated biotic resources, socioeconomic attributes, and geoenvironmental diversity into a georeferenced database. Results reveal a high oil sensitivity of the bay, with approximately 89 % of the mapped coast scoring ESI 8 and ESI 10. These scores comprise, respectively, estuarine and solid substrate habitats that are sheltered from wave action. Notably, numerous manufacturing and oil handling plants, along with intensive urbanization, also contribute to the bay's oil sensitivity. Additionally, the rich biotic diversity in the study area, particularly in protected areas housing 79 conservation units, further amplifies its environmental vulnerability. This study aims to serve as a reference for detailed ESI mapping of coastal areas in tropical rainy zones with significant environmental diversity, industrial development, and a dense population.
Keywords: Costal management; Environmental Sensitivity Index; Guanabara Bay, Brazil; Oil pollution